META-DESIGN: A MANIFESTO FOR END-USER DEVELOPMENT. - Fischer, G.; Giaccardi, E.; Ye, Y.; Sutcliffe, A. G.; Mehandjiev, N. (Communications of the ACM, 2004)
End-user development (EUD) activities range from customization to component configuration and programming. Office software, such as the ubiquitous spreadsheet, provides customization facilities, while the growth of the Web has added impetus to end-user scripting for interactive functions in Web sites. In scientific and engineering domains, end users frequently develop complex systems with standard programming languages such as C++ and Java. However, only a minority of users adapt commercial off-the-shelf (COTS) software products. Indeed, composing systems from reusable components, such as enterprise resource planning (ERP) systems, defeats most end users who resort to expensive and scarce expert developers for implementation.